Mengkaji Lex Spesialis Undang-Undang Anggaran Pendapatan dan Belanja Negara dalam Konteks Pembentukan Peraturan Perundang-undangan - Songga Aurora Abadi (Sultan Jurisprudence: Jurnal Riset Ilmu Hukum, 2021)
This journal discusses the lex specialist of the State Budget (APBN) in the Context of the Formation of Laws and Regulations, with the aim to know concretely how the difference in the process of drafting the APBN Law with other Laws, understands the nature of the substance of the regulation The National Budget and its implications for other laws, in terms of the concept of forming legislation both formally and materially. This research was conducted using qualitative research, through a normative legal research approach (normative legal research), the data were analyzed prescriptive. The data used are secondary data, namely literature studies in the form of laws, books and articles which are related to the writing of this journal. The results showed that the determination of the APBN was not an act of legislation formation (geen daan van wetageving) but an act of government (daad van bestuur). This is because the APBN stipulated in the form of the law is periodic, it only binds the government, and the DPR's right in the formulation of the APBN Law is a budget / budget right. In the formal and material meaning, the APBN law is different from other laws, which formally the APBN law has an element of "periodicity" and an element of "continuity" and materially the APBN law is not binding on the general and only binds the government along with the apparatus and institutions and the Ministry of State.